The Stellarium Gornergrat: Astrophysics with your own Data - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Nordine, Jeffrey; Riesen, Timm-Emanuel (Journal of Physics: Conference Series)
Abstract Remote-controlled telescopes in education provide the opportunity to obtain high quality astronomy images for a broad variety of users. The Stellarium Gornergrat is such a telescope. In addition to pure observation, it offers a user-friendly interface and teaching modules so that astronomical and astrophysical projects can be integrated into everyday school life without any special prior knowledge and without requiring a lot of time. This contribution presents the Stellarium project and a provides an overview of several teaching activities.
Keywords: Computer Science Applications; History; Education

Cross-project empirical and criteria-oriented analysis of pre-service physics teachers’ pedagogical content knowledge Empirisch-kriterienorientierte Analyse des fachdidaktischen Wissens angehender Physiklehrkräfte - Zeller, Jannis; Schiering, Dustin; Kulgemeyer, Christoph; Neumann, Knut; Riese, Josef; Sorge, Stefan (Unterrichtswissenschaft)
Zusammenfassung In den letzten Jahren wurde das Professionswissen (angehender) Lehrkräfte intensiv untersucht. Neben Aussagen zur inneren Struktur liegen auch Ergebnisse über den Zusammenhang zwischen Professionswissen, Performanz in prototypischen Handlungssituationen sowie Unterrichtserfolg vor. In diesen Analysen hat sich gezeigt, dass insbesondere dem fachdidaktischen Wissen eine zentrale Rolle zukommt. Es mangelt bisher jedoch an empirisch fundierten Beschreibungen von Niveaustufen des fachdidaktischen Wissens. Zwar liegen einzelne Vorschläge vor, diese sind jedoch entweder empirisch nicht fundiert oder post hoc generiert, so dass unklar ist, inwieweit die Beschreibung der Ausprägungen auch außerhalb der jeweiligen Projektkontexte anwendbar ist. Der vorliegende Artikel stellt eine projektübergreifende Analyse des fachdidaktischen Wissens mithilfe zweier Ansätze zur Bildung von Niveaustufen vor. Dazu werden Niveaumodelle mit Daten zum fachdidaktischen Wissen aus zwei Projekten ( $$N=427$$ N = 427 und $$N=779$$ N = 779 ) mithilfe des Scale-Anchoring-Verfahrens sowie eines regressionsanalytischen Ansatzes auf Basis eines Modells hierarchischer Komplexität erstellt. Das Scale-Anchoring-Verfahren liefert Niveaubeschreibungen, die sich zwar bezüglich fachlicher und fachdidaktischer Inhalte unterschieden, aber Parallelen bezüglich lernpsychologisch interpretierbarer Operatoren zeigten. Projektübergreifend deuteten die Ergebnisse daraufhin, dass sich das fachdidaktische Wissen in niedrigen Ausprägungen auf reproduktive Aspekte beschränkt, in höheren Ausprägungen aber kreative und evaluierende Elemente hinzukommen. Das Modell hierarchischer Komplexität zeigte sich nur für einen der Datensätze als geeignet, um ein Niveaumodell abzuleiten und konnte daher für projektübergreifende Analysen nicht weiter genutzt werden. Nichtsdestotrotz lieferte die projektübergreifende Analyse mithilfe des Scale-Anchoring-Verfahrens kontextunabhängige Beschreibungen von Ausprägungen des fachdidaktischen Wissens und ermöglicht so erste Schritte in Richtung eines empirisch fundierten, inhaltlich reichhaltigen Assessments, welches über eine Einordnung mittels eines Scores hinaus geht.
Keywords: Education

Empowering Students for the Data-Driven World: A Qualitative Study of the Relevance of Learning about Data-Driven Technologies - Höper, Lukas; Schulte, Carsten (Informatics in Education)
In K-12 computing education, there is a need to identify and teach concepts that are relevant to understanding machine learning technologies. Studies of teaching approaches often evaluate whether students have learned the concepts. However, scant research has examined whether such concepts support understanding digital artefacts from everyday life and developing agency in a digital world. This paper presents a qualitative study that explores students’ perspectives on the relevance of learning concepts of data-driven technologies for navigating the digital world. The underlying approach of the study is data awareness, which aims to support students in understanding and reflecting on such technologies to develop agency in a data-driven world. This approach teaches students an explanatory model encompassing several concepts of the role of data in data-driven technologies. We developed an intervention and conducted retrospective interviews with students. Findings from the analysis of the interviews indicate that students can analyse and understand data-driven technologies from their everyday lives according to the central role of data. In addition, students’ answers revealed four areas of how learning about data-driven technologies becomes relevant to them. The paper concludes with a preliminary model suggesting how computing education can make concepts of data-driven technologies meaningful for students to understand and navigate the digital world.
Keywords: Computer Science Applications; Communication; Education; General Engineering

Personalizing real‐world problems: Posing own problems increases self‐efficacy expectations, intrinsic value, attainment value, and utility value - Schoenherr, Johanna (British Journal of Educational Psychology)
Abstract Background Real‐world problems are important in math instruction, but they do not necessarily trigger students' task motivation. Personalizing real‐world problems by (1) matching problems to students' shared living environment (context personalization) and (2) asking students to pose their own problems (active personalization) might be two interventions to increase students' task motivation. Aim In the current study, we investigated the effects of context personalization and active personalization on students' self‐efficacy expectations, intrinsic value, attainment value, utility value, and cost. Sample The participants were 28 fifth‐ and sixth‐grade students who voluntarily took part in a six‐month afterschool program in which they posed problems with the aim of creating a math walk in their hometown. Method Using a within‐subjects design, at the end of the afterschool program, the students rated their self‐efficacy expectations and task values for four self‐developed problems associated with their hometown, four peer‐developed problems associated with their hometown, and four instructor‐provided problems associated with unfamiliar locations. Results Students reported higher self‐efficacy expectations, intrinsic value, attainment value, and utility value for active‐personalized than non‐personalized problems. To a lesser extent, context personalization promoted intrinsic value and attainment value. No effect was found for cost. Conclusions Active personalization (i.e. asking students to pose their own real‐world problems) is suited to enhance students' task motivation, specifically their self‐efficacy expectations, intrinsic value, attainment value, and utility value. Context personalization still boosts students' intrinsic value and attainment value. Implementation in classroom instruction is discussed.
Keywords: Developmental and Educational Psychology; Education

Does Augmented Reality Help to Understand Chemical Phenomena during Hands-On Experiments?–Implications for Cognitive Load and Learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed Ahmed; da Silva, Ana Alexandra Morim; Pestryakova, Svetlana; Ahmed, Abdullah Fathi; Niemann, Sven; Ngomo, Axel-Cyrille Ngonga (Scientific Data)
Abstract Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project ( Ingrid ) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid , the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present Ingrid KG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update Ingrid KG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of Ingrid KG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.
Keywords: Library and Information Sciences; Statistics; Probability and Uncertainty; Computer Science Applications; Education; Information Systems; Statistics and Probability

How authenticity impacts validity: Developing a model of teacher education assessment and exploring the effects of the digitisation of assessment methods Über Validität und Authentizität: Effekte des Transfers von Testinstrumenten in ein digitales Format auf die erhobenen Aspekte der professionellen Handlungskompetenz - Kulgemeyer, Christoph; Riese, Josef; Vogelsang, Christoph; Buschhüter, David; Borowski, Andreas; Weißbach, Anna; Jordans, Melanie; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Abstract Based on a literature review of studies on teachers’ professional competence and related assessment tools, this paper introduces a model of teacher education assessment. It is influenced by Miller’s (1990) framework of assessment in medical education and includes, among other aspects, performance assessments. This model is used to understand the potential effects of transferring assessment tools into a digital format with assessment feedback. Five examples for such a transfer will be discussed: three methods for various aspects of communication, a test for pedagogical content knowledge, and a test for content knowledge. All five are established instruments well-described in terms of validity. All five have recently been transferred into a digital format. The analysis of this transfer also reveals a potentially harmful effect of digital assessment. The closer an assessment instrument is to assessing action-related parts of professional competence, the more authenticity is required; however, digitisation tends to decrease this authenticity. This suggests that an increasing number of digital assessment tools in teacher education might result in an even more dominant focus on knowledge tests, ignoring other parts of professional competence. This article highlights the role of authenticity in validity and discusses the most suitable assessment format to address various parts of professional competence. It ends by highlighting the lessons learned from the transfer of assessment instruments into a digital format that other academic disciplines might find interesting.
Keywords: Education

Life-cycle health effects of compulsory schooling - Schmitz, Hendrik; Tawiah, Beatrice Baaba
We study the effect of education on health (hospital stays, number of diagnosed conditions, self-rated poor health, and obesity) over the life-cycle in Germany, using compulsory schooling reforms as a source of exogenous variation. Our results suggest a positive correlation of health and education which increases over the life-cycle. We do not, however, find any positive local average treatment effects of an additional year of schooling on health or health care utilization for individuals up to age 79. An exception is obesity, where positive effects of schooling start to be visible around age 60 and become very large in age group 75-79. The results in age group 75-79 need to be interpreted with caution, however, due to small sample size and possible problems of attrition.
Keywords: Education; health; life-cycle effects; compulsory schooling

The effect of compulsory schooling on vaccination against COVID and Influenza - Monsees, Daniel; Schmitz, Hendrik
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination.
Keywords: COVID; influenza; vaccination; education; compulsory schooling

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science

Comparison of Required Competences and Task Material in Modeling Education - Soyka, Chantal; Ullrich, Meike; Striewe, Michael; Schaper, Niclas (Enterprise Modelling and Information Systems Architectures)
The reform of the European academic landscape with the introduction of bachelor's and master's degree programs has brought about several profound changes for teaching and assessment in higher education. With regard to the examination system, the shift towards output-oriented teaching is still one of the most significant challenges. Assessments have to be integrated into the teaching and learning arrangements and consistently aligned towards the intended learning outcomes. In particular, assessments should provide valid evidence that learners have acquired competences that are relevant for a specific domain. However, it seems that this didactic goal has not yet been fully achieved in modeling education in computer science. The aim of this study is to investigate whether typical task material used in exercises and exams in modeling education at selected German universities covers relevant competences required for graphical modeling. For this purpose, typical tasks in the field of modeling are first identified by means of a content-analytical procedure. Subsequently, it is determined which competence facets relevant for graphical modeling are addressed by the task types. By contrasting a competence model for modeling with the competences addressed by the tasks, a gap was identified between the required competences and the task material analyzed. In particular, the gap analysis shows the neglect of transversal competence facets as well as those related to the analysis and evaluation of models. The result of this paper is a classification of task types for modeling education and a specification of the competence facets addressed by these tasks. Recommendations for developing and assessing student's competences comprehensively are given.
Keywords: conceptual modeling; higher education; competence-oriented assessment; task analysis; graphical modeling

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science

ARIadne – An Explanation Model for Digital Artefacts - Winkelnkemper, Felix; Höper, Lukas; Schulte, Carsten (Informatics in Education)
When it comes to mastering the digital world, the education system is more and more facing the task of making students competent and self-determined agents when interacting with digital artefacts. This task often falls to computing education. In the traditional fields of computing education, a plethora of models, guidelines, and principles exist, which help scholars and teachers identify what the relevant aspects are and which of them one should cover in the classroom. When it comes to explaining the world of digital artefacts, however, there is hardly any such guiding model. The ARIadne model introduced in this paper provides a means of explanation and exploration of digital artefacts which help teachers and students to do a subject analysis of digital artefacts by scrutinizing them from several perspectives. Instead of artificially separating aspects which target the same phenomena within different areas of education (like computing, ICT or media education), the model integrates technological aspects of digital artefacts and the relevant societal discourses of their usage, their impacts and the reasons behind their development into a coherent explanation model.
Keywords: Computer Science Applications; Communication; Education; General Engineering

Primary school teachers’ perspectives on the quality of inclusive education - Görel, Gamze; Franzen, Katja; Hellmich, Frank (Teachers and Teaching)
Keywords: Arts and Humanities (miscellaneous); Education

Riegel, Ulrich / Zimmermann, Mirjam (2022). Evaluation des konfessionell-kooperativen Religionsunterrichts in Nordrhein-Westfalen. Stuttgart: Kohlhammer. ISBN 978-3-17-043134-8. 333 Seiten. - Hüster, Jonas Maximilian (Religionspädagogische Beiträge)
Keywords: Religious studies; Education

The data awareness framework as part of data literacies in K-12 education - Höper, Lukas; Schulte, Carsten (Information and Learning Sciences)
In today's digital world, data-driven digital artefacts pose challenges for education, as many students lack an understanding of data and feel powerless when interacting with them. This article addresses these challenges and introduces the data awareness framework. It focuses on understanding data-driven technologies and reflecting on the role of data in everyday life. The paper also presents an empirical study on young school students' data awareness. The study involves a teaching unit on data awareness framed by a pretest-posttest design using a questionnaire on students' awareness and understanding of and reflection on data practices of data-driven digital artefacts. The study's findings indicate that the data awareness framework supports students in understanding data practices of data-driven digital artefacts. The findings also suggest that the framework encourages students to reflect on these data practices and think about their daily behaviour. Students learn a model about interactions with data-driven digital artefacts and use it to analyse data-driven applications. This approach appears to enable students to understand these artefacts from everyday life and reflect on these interactions. The work contributes to research on data and AI literacies and suggests a way to support students in developing self-determination and agency during interactions with data-driven digital artefacts.
Keywords: Library and Information Sciences; Computer Science Applications; Education

Post-pandemic online mathematics and statistics support: Practitioners’ opinions in Germany and Great Britain & Ireland - Gilbert, H.; Schürmann, M.; Liebendörfer, M.; Lawson, D.; Hodds, M. (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Professional Development Enacted by Facilitators in the Context of Early Mathematics Education: Scaling up or Dilution of Effects? - Bruns, Julia; Hagena, Maike; Gasteiger, Hedwig (Teaching and Teacher Education)
Keywords: Education

Implementing profession orientation as a design principle for overcoming Klein’s second discontinuity – preservice teacher’s perspectives on interface activities in the context of a geometry course - Hoffmann, Max; Biehler, Rolf (ZDM – Mathematics Education)
Intending to counteract Klein’s second discontinuity in teacher education, we explored and applied the innovation of “interface ePortfolio” in the context of a geometry course for preservice teachers (PSTs). The tool offers the possibility of implementing the design principle of profession orientation. In the article, we theoretically clarify what we understand by this principle and locate our innovative concept against this theoretical background. We empirically investigate the extent to which counteraction against the second discontinuity is successful by analyzing reflection texts created in the interface ePortfolio, focusing on PSTs’ perspectives. Our qualitative content analysis shows that most of them perceive the innovation as helpful in the intended sense and indicates that the course concept, in general, and the interface ePortfolio, in particular, have helped establish relevant links between the course content and their later work as teachers.
Keywords: General Mathematics; Education

Fostering students’ peer relationships through the classroom-based intervention FRIEND-SHIP. Education 3-13 - Hassani, S.; Jakob, K.; Schwab, S.; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze (International Journal of Primary, Elementary and Early Years Education.)
Keywords: Life-span and Life-course Studies; Education